2019
DOI: 10.1002/hep.30572
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Postoperative Liver Dysfunction Based on Blood‐Derived MicroRNA Signatures

Abstract: There is an urgent need for an easily assessable preoperative test to predict postoperative liver function recovery and thereby determine the optimal time point of liver resection, specifically as current markers are often expensive, time consuming, and invasive. Emerging evidence suggests that microRNA (miRNA) signatures represent potent diagnostic, prognostic, and treatment‐response biomarkers for several diseases. Using next‐generation sequencing as an unbiased systematic approach, 554 miRNAs were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…In addition, more details on the variables of patients' characteristics should be included in this study. Clarification about the omissions we mention would greatly solidify the conclusions of the study by Starlinger et al (1) Haisu Dai, M.D. Kaicheng Shen, M.D.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…In addition, more details on the variables of patients' characteristics should be included in this study. Clarification about the omissions we mention would greatly solidify the conclusions of the study by Starlinger et al (1) Haisu Dai, M.D. Kaicheng Shen, M.D.…”
supporting
confidence: 79%
“…Indeed, plasma albumin levels significantly differed between patients with and without liver dysfunction (LD) in our exploration cohort. (1) As mentioned by the authors, it is already known that decreased plasma albumin levels correlate with perioperative outcome. However, we feel quite confident about our results, as we were able to validate the predictive potential of our microRNA (miRNA) signature in an independent validation cohort in whom no significant differences in albumin levels were observed.…”
Section: Replymentioning
confidence: 92%
“…The study by Starlinger et al (1) reported that they have found microRNA (miRNA)-based biomarkers, which could reliably predict postoperative liver dysfunction (LD) after liver resection and dynamically monitor liver function recovery and might represent a very useful tool to define the most suitable time point for liver resection to avoid postoperative LD and complications. More importantly, they showed superior prognostic performance when compared to currently used clinical markers for prediction of postoperative LD.…”
Section: To the Editormentioning
confidence: 99%
“…We read with interest the study of Starlinger et al (1) evaluating the ability of microRNA signatures to predict postoperative liver dysfunction in patients with liver cancer. The results showed that it could effectively predict postoperative liver dysfunction.…”
Section: Letter To the Editor: Predicting Postoperative Liver Dysfuncmentioning
confidence: 99%
See 1 more Smart Citation